Do retail investors care about ESG ratings? - Bennet Janssen; Youpeng Zhang (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
This paper examines the causal impact of ESG ratings and their divergence on retail investors' sustainable investment decisions. Using a survey with a framed choice experiment conducted with 2,025 German retail investors, we document three key findings: (i) While about two in three investors claim they own sustainable equity funds, merely six percent actively incorporate ESG ratings into their own portfolio decisions; (ii) the sustainable investment is associated with the respondents' beliefs, motivations, and expectations; (iii) higher average ESG ratings increase investment in sustainable funds, but rating divergence reduces such allocations. We formally show that the results are consistent with an ESG portfolio choice model in which ESG rating divergence acts as noisy signals of sustainability and investors differ in their responsiveness based on rating credibility, sustainability preferences, and risk-return expectations. We provide further robust evidence that, while ESG rating divergence has a weaker effect on committed ESG investors, it significantly reduces the likelihood of sustainable investments among retail investors with lower exposure to green assets.
Keywords: G11; D14; G24; G41; G51; D83; 330; Sustainable Finance; Portfolio Choices; ESG Ratings; Uncertainty; Investment Decisions